Long COVID outcomes following omicron wave in non-hospital population - Ruiyin, Wang; Qi, Jia; Tingting, Wang; Yuqin, Yan; Yan, Jia; Kun, Peng (Frontiers in Public Health, 2024)
Background The persistence of symptoms or the development of new symptoms following a diagnosis of SARS-CoV-2 has given rise to a multifaceted clinical condition referred to as “long COVID” (LC). The understanding of LC among China’s non-hospitalized population continues to be insufficient. This investigation was designed to evaluate the protracted consequences amongst this demographic, as well as to identify the associated risk factors. Methods This research constitutes a prospective cohort study focusing on non-hospitalized individuals, aged between 18 and 59, who have been positively diagnosed with COVID-19. Each participant was subjected to a sequence of questionnaire-based surveys, designed to evaluate symptoms as well as the status of depression and anxiety. A logistic regression model, adjusted for multiple variables, was employed to scrutinize the correlation between demographic elements, lifestyle attributes, and health-related risk factors in relation to conditions and symptoms post COVID-19 infection. Results A total of 706 individuals participated in the 3 months follow-up, with 620 continuing on to the 6 months follow-up. The median age was 35 (28, 43) years, and 597 (85%) are female. Upon follow-up, Compared with patients without LC, patients with LC have a higher proportion of females (420 (87%) vs. 177 (79%); p = 0.010), were older (35 (29, 44) years vs. 33 (27, 41) years; p = 0.010) and have more comorbidities. Out of all participants, 483 (68.4%) reported experiencing at least one symptom at the 3 months mark, while 49.7% reported symptoms persisting at the 6 months mark. At the 3 months follow-up, the most prevalent persistent symptoms were cough (46%), fatigue (38%), and shortness of breath (34%). By the 6 months follow-up, fatigue (25%), shortness of breath (22%), and sleep disorders (16%) were the most commonly reported symptoms. Anxiety and depression were consistently reported as prevalent symptoms throughout the follow-up period. Most patient symptoms fade over time, with the quickest decreases observed in cough (from 46 to 9%), expectoration (from 26 to 6.3%), smell disorder (from 16 to 3.9%), and taste disorder (from 18 to 3.5%). Male and those possessing advanced educational qualifications exhibit a decreased susceptibility to the sustained incidence of coughing. Conversely, older age and the presence of comorbidities were identified as risk factors for persistent fatigue and shortness of breath. Conclusion In the after of COVID-19, it has been observed that the majority of patient symptoms tend to decrease over time. The primary residual symptoms noticed after a 6 month follow-up were fatigue, dyspnea, and sleep disturbances. However, it’s noteworthy that the risk factors associated with these symptoms exhibit subtle variations. Furthermore, psychological sequelae, namely depression and anxiety, are frequently reported among COVID-19 survivors.